KOMPARASI PENAKSIRAN PENJUALAN DENGAN METODE TREND MOMENT DAN LEAST SQUARE PADA PT. ASAHIMAS FLAT GLASS - Qurochman Arief Nurdiannova (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2018)
The purpose of this research was to conduct valuation of sales at PT Asahimas Flat Glass (AMFG) by the method of least square moment and trend. The data used in this study is taken from website of the IDX data in particular net sales from the company's beginning in 2010 until the year 2017. Calculation based on estimates of sales according to the trend of the moment and least square, retrieved the same estimate figures for the years 2018, 2019, 2020 and. In addition, based on the standard error estimates (Mean Forecast Error) or the estimated figures, MFE expressed accurately due to the valuation standard MFE is zero or close to zero.